Respuestas

  • Usuario de Brainly
2013-03-15T13:17:06+01:00

Resolvamos :

 

(x + 2)/(x -1) - (x+3)/(x+1) = (2x +2)/( x^2  -1)

 

Saquemos MCM de [ (x -1) , ( x+1) ] =   (x-1)*(x+1)

 

    [ (x+2)*(x+1) - (x+3)*(x-1) ]                     ( 2x +2)

-----------------------------------------   =     -------------------------

              (x-1)(x+1)                                          ( x^2   -1 )

 

Recordemos esta propieDaD : 

( a+b) * (a-b) = a^2  -   b^2

 

Ahora sigamos operando :

 

    [ x^2 + x +2x +2 - (  x^2 -x +3x -3) ]                       ( 2x +2)

-------------------------------------------------------  =   --------------------------

               ( x^2  -1  )                                                          ( x^2  -1  )  

 

Eliminamos en ambos mienbros " x^2  -1 " y nos queDa :

 

 [ x^2 +3x +2 -x^2 +x -3x +3 ] = (2x +2)

 x^2 +3x +2 -x^2   -2x +3 [ =  ( 2x +2 )

         3x +2 -2x +3 = 2x +2

                 x +5 = 2x +2

               x -2x = 2 -5

                  -x =  -3

                    x = 3

 

Rpta "  3 ".

 

Un SaLuDo :)''

 

 

 

 

2013-03-15T16:07:47+01:00

(x+2)(x+1)(x+3)(x-1)=(1)(2x+2)

------------------------------------------------=x=-1

  (x-1)(x+1)                     (x-1)(x+1)